Memory and affect in Shakespeare's England - Baldo, Jonathan; Karremann, Isabel (Cambridge University Press, 2023)
This is the first collection to systematically combine the study of memory and affect in early modern culture. Essays by leading and emergent scholars in the field of Shakespeare studies offer an innovative research agenda, inviting new, exploratory approaches to Shakespeare's work that embrace interdisciplinary cross-fertilization. Drawing on the contexts of Renaissance literature across genres and on various discourses including rhetoric, medicine, religion, morality, historiography, colonialism, and politics, the chapters bring together a broad range of texts, concerns, and methodologies central to the study of early modern culture. Stimulating for postgraduate students, lecturers, and researchers with an interest in the broader fields of memory studies and the history of the emotions - two vibrant and growing areas of research - it will also prove invaluable to teachers of Shakespeare, dramaturges, and directors of stage productions, provoking discussions of how convergences of memory and affect influence stagecraft, dramaturgy, rhetoric, and poetic language